2018
DOI: 10.3389/fped.2018.00346
|View full text |Cite
|
Sign up to set email alerts
|

Early Inflammatory Markers for the Diagnosis of Late-Onset Sepsis in Neonates: The Nosodiag Study

Abstract: Background: Early diagnosis is essential to improve the treatment and prognosis of newborn infants with nosocomial bacterial infections. Although cytokines and procalcitonin (PCT) have been evaluated as early inflammatory markers, their diagnostic properties have rarely been compared.Objectives: This study evaluated and compared the ability of individual inflammatory markers available for clinician (PCT, semi-quantitative determination of IL-8) and of combinations of markers (CRPi plus IL-6 or quantitative or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…The low level of bacteremia, as well as the insufficient volume taken for blood tests, especially in children with extremely low body weight, may be one of the explanations for a large number of cases of culture-negative sepsis. In addition, antibiotic treatment in the mother before or during childbirth may in some cases mask the detection of bacteremia in the newborn [15]. In cases where the blood cultures and other sterile cultures are negative, but the child shows signs that correspond to the implementation of the infectious process, they can be considered "clinical" sepsis [16].…”
Section: Discussionmentioning
confidence: 99%
“…The low level of bacteremia, as well as the insufficient volume taken for blood tests, especially in children with extremely low body weight, may be one of the explanations for a large number of cases of culture-negative sepsis. In addition, antibiotic treatment in the mother before or during childbirth may in some cases mask the detection of bacteremia in the newborn [15]. In cases where the blood cultures and other sterile cultures are negative, but the child shows signs that correspond to the implementation of the infectious process, they can be considered "clinical" sepsis [16].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was also found that WBC, N% and hs-CRP were transiently increased at T0 and were most significantly increased at T1, which is consistent with the results of a number of experiments ( 14 , 15 ). CRP is an acute-phase reactive protein and an important inflammatory marker, which will obviously increase in the case of acute inflammation and trauma in the body ( 16 ). With the application of anti-inflammatory and anti-infective drugs after operation and inflammation control, CRP gradually declines, and the body temperature also gradually drops to normal.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α increased sharply after the injection of LPS, followed by the increase of IL-6, while TNF-α decreased rapidly in vivo (Michie et al 1988;Fong and Lowry 1990). However, the level of IL-6 in plasma is considered to be more valuable for the prediction of mortality (Sullivan et al 1992) and nosocomial infection (Dillenseger et al 2018). Kumar et al (1999) found that TNF-α, IL-6 and other inflammatory factors had inhibitory effect on the contraction of cardiomyocytes, which was positively correlated with the dose.…”
Section: Effect Of Apelin-13 On Lps-induced Simdmentioning
confidence: 99%